Study of Polarized Wave with a Hydrodynamic Model and Fourier Spectral Method. (12th December 2013) - Ching, Dennis Ling Chuan; Abdul Aziz, Zainal; Salah, Faisal
Abstract : The polarization effects in hydrodynamics are studied. Hydrodynamic equation for the nonlinear wave is used along with the polarized nonlinear waves and seismic waves act as initial waves. The model is then solved by Fourier spectral and Runge-Kutta 4 methods, and the surface plot is drawn. The output demonstrates the inundation behaviors. Consequently, the polarized seismic waves along with the polarized nonlinear waves tend to generate dissimilar inundation which is more disastrous.